Strengthening the Capacity of Immigration Officers in Passport Interviews as a Strategy to Prevent Trafficking in Women: A Systematic Literature Review - Mailan, Ruly; Hanita, Margaretha; Nita, Surya (Riviera Publishing, 2025)
Human trafficking, particularly of women, remains a growing and complex transnational crime. Indonesia plays a strategic role in preventing trafficking through its immigration system, where immigration officers are key in identifying potential victims via gender-based passport interviews. This study systematically reviews literature on gender-based interview methods to evaluate their effectiveness in early detection and prevention of trafficking in women. Using the PRISMA protocol, nine relevant studies from major databases were analyzed, focusing on psychological trauma, passport procedures, and multi-stakeholder collaboration. Findings highlight challenges such as limited gender sensitivity in current immigration interviews and emphasize the need for specialized officer training. The research underscores the importance of integrating trauma-informed approaches and community-based policies to enhance detection and protection mechanisms. Strengthening immigration officers' capacity through continuous training and cooperation with international organizations and NGOs is crucial. This literature synthesis provides practical recommendations to improve immigration interview protocols and supports policy development aimed at reducing women’s vulnerability to trafficking, especially in Indonesia’s border regions. The study contributes a comprehensive framework for enhancing immigration responses to human trafficking, promoting early victim identification, and fostering collaborative prevention efforts.